2007
DOI: 10.1016/j.febslet.2007.06.066
|View full text |Cite
|
Sign up to set email alerts
|

Response of the central metabolism of Escherichia coli to modified expression of the gene encoding the glucose‐6‐phosphate dehydrogenase

Abstract: The deletion of the zwf gene encoding G6PDH activity led to restructuring of the carbon flux through central metabolism in Escherichia coli, though over-expression of this gene had only minor consequences for overall carbon flux. The modified carbon flux seen in the zwf deletion mutant enabled alternative routes of anabolic precursor formation and an adequate supply of NADPH synthesis via a modified TCA cycle to be generated so as to sustain growth rates comparable to the WT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
62
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 25 publications
12
62
0
Order By: Relevance
“…The genetic perturbation experiments showed that out of 60 metabolic genes, only 3 were lethal and 5 affected strongly the growth rate on glucose. Consistent with previous work (29,37,42), these results highlight the robustness of E. coli metabolism despite loss of a single enzyme in central carbon metabolism. Thanks to physiological descriptors, we were able to reveal not only the phenotype of silent mutations, in terms of growth, but also the phenotype of gene deletion mutants not directly involved in central metabolism (i.e., transcription and sigma factors).…”
Section: Discussionsupporting
confidence: 80%
“…The genetic perturbation experiments showed that out of 60 metabolic genes, only 3 were lethal and 5 affected strongly the growth rate on glucose. Consistent with previous work (29,37,42), these results highlight the robustness of E. coli metabolism despite loss of a single enzyme in central carbon metabolism. Thanks to physiological descriptors, we were able to reveal not only the phenotype of silent mutations, in terms of growth, but also the phenotype of gene deletion mutants not directly involved in central metabolism (i.e., transcription and sigma factors).…”
Section: Discussionsupporting
confidence: 80%
“…F6P is a precursor for a range of biomolecules, including peptidoglycan and lipid A, and cannot be used as a substrate for glycolysis because the Caulobacter genome does not encode a phosphofructokinase (9). It has been shown experimentally that decreased zwf expression in Escherichia coli modulates carbon flux through central metabolic pathways, resulting in increased concentrations of F6P (29). Similarly, synthesis of the exopolysaccharide alginate in Pseudomonas aeruginosa requires F6P as a precursor (38).…”
Section: Vol 192 2010 Genetic Basis Of Caulobacter Adaptation 3683mentioning
confidence: 99%
“…In the case of the partitioning of the flux around glucose-6-phosphate, it was observed that it does change after an increase in the demand (Rui et al, 2010) or the offer of NADPH (Martínez et al, 2008). To the best of our knowledge, there are no studies on how much control EcG6PDH could exert upon the flux through the oxPPP, although increasing its concentration above the typical level did not increase significantly the flux through this pathway (Nicolas et al, 2007;Orthner & Pizer, 1974). …”
Section: Design and Kinetic Study Of An Nad-preferring G6pdhmentioning
confidence: 99%